YIELD SURFACE OF MU-SAN SANDSTONE BY HOLLOW CYLINDER TESTS - Lee D.H.; Juang C.H.; Lin H.M. (My University, 2002)
The failure behavior of rocks can be quite complex, affected by such factors as stress path, anisotropy, and loading types and conditions. To understand the mechanical behavior of rocks under complex field conditions, the true triaxial test and hollow cylinder test was employed. This paper conducts additional hollow cylinder tests with different confining pressures, and with improved accuracy.